Skills in African Labor Markets and Implications for Migration to Europe - Andreas Backhaus (Kiel Institute for the World Economy (IfW), 2020)
This paper assesses the potential for skilled labor migration from sub-Saharan Africa to Europe. It utilizes representative surveys from Ghana and Kenya to shed light on the quality and distribution of skills in the labor markets of these countries. Skills in both countries are found to be unevenly distributed, with significant parts of the labor force being essentially unskilled. Similarly designed surveys from France, Germany, and the UK further allow comparing skills and formal education between the African and the European countries. On average, the labor force in the subSaharan African countries is less skilled and less educated than the European labor force. Importantly, even at the same levels of formal education, workers in Ghana and Kenya are substantially less skilled than workers in Europe. The paper further considers a number of hypothetical scenarios for skilled labor migration from the African to the European countries. It is demonstrated that the European countries would have to recruit workers from the very top end of the African skill distribution to match European demands for skills. In turn, the average worker from the African labor markets would fit only into the low end of the European skill distribution where employment rates are low. Hence, more regular and skilled labor migration from African countries will unlikely be a remedy for skill shortages in Europe unless migrants are positively selected on their skills. In that case, however, additional opportunities for skilled labor migration would risk a brain drain from African countries that could harm economic development there. Improving the quality of education in sub-Saharan Africa on a broad scale remains indispensable for mutually beneficial migration between Africa and Europe.
Keywords: I25; J61; O15; 330; migration; skills; human capital; brain drain; sub-Saharan Africa; Europe